(untitled) (Research, Society and Development, 2020)
Introduction: The hamstrings correspond to a set of three muscles located in the posterior region of the thigh, being one of the most injured muscle groups in sports invironment. Whit this, Nordic hamstring exercice (NHE) emerges as an alternative, aiming to increase muscle strength and prevent injuries, being a low-cost intervention, since it does not necessarily require the use of equipment. Objective: To perform na integrative review on the effects of Nordic exercice on the prevetion of hamstring injuries in soccer players. Material and method: The elaboration of this integrative review was based on articles related to the health sector and published between the years 2009 and 2019, based on randomized clinical trials and available in English, exluding review articles, meta-analyses and systematic reviews. The virtual health library (VHL), PUBMED and PEDro platform was used as the basis for data collection. The Keywords used for the research where: hamstring muscles, nordic exercice and soccer. Results: 326 articles where found using the keywords mentioned above. After fulfílling all the ellegibility criteria, 7 articles where select to composse the review. The information obttained presentes positive results of ENI on the reduction of hamstring injury rates of soccer players. Conclusion: Based on the data obtained in this reseach, it was possible to state that NHE presents satisfactory results in reducing the incidence of lesions in the hamstring injuries as well as decreasing recurrence rates. Thus, it can contributed to the academic environmet and other health professional, corroborating for a more scientifically based practice.